Analysis of Athletes' Knowledge Level About Injury Risk in Fencing at Kudus Regency - Hasnaa Khoirun Nisa; Taufiq Hidayah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Abstract  _________________________________________________________________ This study aims to analyze the level of knowledge of fencing athletes regarding injury risk in Kudus Regency. The research employed a quantitative approach with a descriptive survey method. The study population consisted of 30 fencing athletes registered under IKASI Kudus Regency, with a sample of 25 athletes selected using purposive sampling technique. The research instrument used a questionnaire adopted from Kurniadi (2024) consisting of 40 statement items that had been tested for validity (0.520) and reliability (0.750). Data analysis used descriptive statistics with the help of SPSS-23. The results showed that the overall knowledge level of athletes was in the fair category with a mean score of 28.00 out of 40 (70%). Based on frequency distribution, 11 athletes (44%) were in the good category, 11 athletes (44%) in the fair category, and 3 athletes (12%) in the poor category. Regarding the sports injury knowledge indicator, 12 athletes (48%) were in the good category, 11 athletes (44%) in the fair category, and 2 athletes (8%) in the poor category. Regarding the injury handling knowledge indicator, 11 athletes (44%) were in the good category, 13 athletes (52%) in the fair category, and 1 athlete (4%) in the poor category. Regarding the injury prevention knowledge indicator, all athletes (100%) were in the poor category. The conclusion of this study is that the overall knowledge level of fencing athletes in Kudus Regency regarding injury risk is in the fair category, but knowledge about injury prevention remains very low. It is recommended that coaches, clubs, and sports administrators systematically and continuously enhance education on injury prevention.